Comparative Advertising: Effects of Structural Alignability on Target Brand Evaluations - Zhang, Shi; Kardes, Frank R.; Cronley, Maria L. (Journal of Consumer Psychology, 2002)
Structural alignability refers to the readiness with which the attributes of one brand can be mapped on to those of another brand. Across three experiments, we show that as alignability in comparative advertising decreases, advertising‐induced target brand evaluations also decrease. This effect is explained by the extent to which assumptions about attribute comparisons are needed. We further show that the effect of alignability on evaluation is moderated by the need for cognitive closure, an individual difference variable that influences preferences for easy comparison and less ambiguity. Although prior research has treated alignability as a dichotomous variable (present or absent), the research presented here suggests that there are different types of (non)alignability comparisons.